MiR-10b is a prognostic marker in clear cell renal cell carcinoma. Issue 10 (30th March 2017) - Khella, Heba W Z; Daniel, Nicole; Youssef, Leza; Scorilas, Andreas; Nofech-Mozes, Roy; Mirham, Lorna; Krylov, Sergey N; Liandeau, Evi; Krizova, Adriana; Finelli, Antonio; Cheng, Yufeng; Yousef, George M
Abstract : Aims: Clear cell renal cell carcinoma (ccRCC) is the most common adult kidney cancer. It is an aggressive tumour with unpredictable outcome. The currently used clinical parameters are not always accurate for predicting disease behaviour. miR-10b is dysregulated in different malignancies including RCC. Methods: We assessed the clinical utility of miR-10b as a prognostic marker in 250 patients with primary ccRCC. We examined the correlation between miR-10b and clinicopathological parameters. We compared miR-10b expression among different RCC subtypes and normal kidney tissue. Results: We observed a stepwise decrease of miR-10b expression from normal kidney to primary ccRCC and a further decrease from primary to metastatic RCC. miR-10b expression was significantly lower in stages III/IV compared with stages I/II (p=0.038). Using a binary cut-off, miR-10b-positive patients had significantly longer disease-free survival (HR=0.47, CI 0.28 to 0.79, p=0.004). In the subgroup of patients with tumour size >4 cm, higher miR-10b expression was associated with significant longer disease-free and overall survival (p=0.001 and p=0.036, respectively). miR-10b was significantly downregulated in ccRCC compared with normal kidney (p<0.0001), and oncocytoma (p=0.031). It was also downregulated in chromophobe RCC. In addition, we identified a number of miR-10b-predicted targets and pathways that are involved in tumourigenesis. Conclusions: Our data point to miR-10b as a promising prognostic marker in ccRCC with potential therapeutic applications.